On the Issue of Regional Economic Security in Modern Conditions (on the Example of the Northwestern Federal District). Article One - N. M. Mezhevich; V. A. Shamakhov; A. D. Khlutkov (Управленческое консультирование, 2023)
The article deals with the issues of economic security in the context of the modern interpretation of post-globalization. After analyzing the existing definitions of the concept of “economic security”, the authors came to the conclusion that the implementation of Russia’s national interests and priorities in the economic sphere is impossible without taking into account the regional factor. The Northwestern Federal District is of particular importance for the system of strategic priorities of regional security due to historical, geographical, and economic reasons. A universal understanding of security presupposes a particularly attentive attitude to key regions. Let us point out that this corresponds to all world approaches to understanding economic security